Interfacing PIC microcontrollers : embedded design by interactive simulation - Bates, Martin, 1952- (Oxford : Newnes, 2014)
Interfacing PIC Microcontrollers, 2nd Edition is a great introductory text for those starting out in this field and as a source reference for more experienced engineers. Martin Bates has drawn upon 20 years of experience of teaching microprocessor systems to produce a book containing an excellent balance of theory and practice with numerous working examples throughout. It provides comprehensive coverage of basic microcontroller system interfacing using the latest interactive software, Proteus VSM, which allows real-time simulation of microcontroller based designs and supports the development of new applications from initial concept to final testing and deployment. Comprehensive introduction to interfacing 8-bit PIC microcontrollers Designs updated for current software versions MPLAB v8 & Proteus VSM v8 Additional applications in wireless communications, intelligent sensors and more.
Includes index.
Keywords: Programmable controllers